Feminized Virus: A Content Analysis of Social Media’s Representation of HPV Vaccine - Yiwei Li; Yu Guo; Hong Lin (Social Media + Society, 2022)
Attempting to explore social media’s role in human papillomavirus (HPV) vaccination campaign, the present study concentrated on Weibo , the most popular microblogging service in China, and examined HPV vaccine-related information in 1,221 posts shared within 1½ years, during the time of which two key HPV vaccines were officially launched in the market in mainland China. Results of quantitative content analysis suggested an inadequate and unbalanced framework for the representation of HPV vaccination. More specifically, a majority of information came from non-expert sources; following the extended parallel process model (EPPM), the present study found that comparing with susceptibility and severity of HPV infection, HPV vaccine efficacy tends to be more emphasized with a recommending tone; in the meantime, from a gender perspective, messages on Weibo demonstrated the tendency of gender imbalance, that is, women’s responsibility for preventing sexually transmitted diseases is much more highlighted than men’s, raising concerns over gender inequality in responding to HPV infection.